Mogok Kerja Tenaga Medis: Problematika pada UU Ketenagakerjaan dan Pilihan Model Pengaturannya - Agung, Rama (UI Scholars Hub, 2025)
The issue of healthcare workers' strikes remains complex in terms of regulatory frameworks. On one hand, there is a conflict of interest between public interest in access to healthcare services and, on the other, the Labor Law, which regards the right to strike as a fundamental right of workers, integral to collective bargaining. This paper examines the challenges in regulating healthcare workers' strikes by analyzing Article 139 of the Labor Law and exploring regulatory models that support the provision of high-quality healthcare services. The findings highlight several key points. First, Article 139 of the Labor Law does not yet provide a proportional approach to balancing the right to strike with the right to healthcare. This is due to rigid interpretations of the term